(untitled) (SAARC Journal of Agriculture, 2023)
A field experiment was conducted at the aonla based multistoried agroforestry research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University from June, 2018 to July, 2019 to know the growth performance of dragon fruit and its establishment problems under multistoried tree orchard. The upper storied component of multistoried was aonla tree, carambola and lemon were used as middle storied components, while dragon fruit was the test crop grown as lower storied component. The experiment was laid out in a two-factor randomized complete block design with three replications. Factor A: Production systems (T1: aonla + carambola + lemon + dragon fruit, T2: aonla + dragon fruit, and T3: dragon fruit as sole). Factor B: Two dragon fruit genotypes i.e. red fleshed dragon fruit (V1), and white fleshed dragon fruit (V2). The result indicated that the higher plant height and the maximum number of branches were produced by the red-fleshed dragon fruit than white-fleshed dragon fruit irrespective of production systems. Upper storied plant aonla received 100% PAR but the average amount of light availability for lower storied dragon fruit in the whole growing season was 70.71% (807.51 µmm-2s-1), middle storied carambola and lemon received 77.11% (880.60 µmm-2s-1) and 65.19% (744.47 µmm-2s-1) PAR, respectively. The study found a negative linear relationship between the plant height of dragon fruit and PAR. Only basal rot disease was observed as establishment problem. The maximum disease infestation occurred (37.50%) in multistoried system compared to the sole cropping system (6.94%) and Fusarium oxysporum was identified as causal organism. SAARC J. Agric., 21(1): 39-51 (2023)